Pegaruh Kebiasaan Belajar Aktif Siswa terhadap Prestasi Belajar di Kelas VIII MTS. YPPI Wonorejo Belitang - Astrid, Annisa; Istikomah, Istikomah; Karoma, Karoma (Fitrah: Journal of Islamic Education, 2021)
This study departs from active learning habits that will affect student achievement in MTs schools. YPPI Wonorejo. This study aims to analyze students' active study habits and their effect on student achievement. The method used is quantitative with a descriptive survey approach. The research population is all students grade VIII, totaling 176, of which 100 students are set as samples by using proportionate stratified random sampling technique. Methods of collecting data with questionnaires, unstructured interviews and documentation were analyzed using descriptive statistical analysis, normality test, linearity test, and regression test. The results of the study show that: (1) The level of active learning habits of students is in the good category, this is proven by the mean value of 66.96, median of 65.50, mode of 65, standard deviation of 9.710. (2) Student learning achievement is also in good category, which is the mean 71.70, median 73.00, mode 80, standard deviation 7.175. (3) There is a significant effect between active study habits on student achievement. It is characterized by a significant linear relationship (0.114 > 0.05), and the value of tcount> tÂtable (3.710 > 1.987).